Posttranscatheter Aortic Valve Replacement Ventricular Septal Defect During Transfemoral Edwards SAPIEN Valve Implantation. Issue 11 (1st June 2016) - Dahl, Aaron; Hoaglan, Carli; Helman, James
Abstract : Transcatheter aortic valve replacement (TAVR) is gaining favor as a treatment for aortic stenosis in patients at high risk for the open surgical approach. The following is a report of a 95-year-old woman with severe aortic stenosis who presented for TAVR with an Edwards SAPIEN valve. Her medical history included pacemaker-dependent complete heart block and a recent episode of congestive heart failure secondary to a non-ST segment elevation myocardial infarction. The TAVR was performed successfully through an open left femoral artery approach, and the patient was found to have a new perimembranous ventricular septal defect identified postoperatively. Abstract : Supplemental Digital Content is available in the text.